Defining and Performing the Functions of Extension Mentors - Amy Harder; Savanna Turner (EDIS, 2021)
This new 3-page document provides UF/IFAS Extension faculty serving as formal mentors with information about the three primary functions of a mentor and guidance on how to perform those functions using a mentor calendar. Written by Amy Harder and Savanna Turner and published by the UF/IFAS Department of Agricultural Education and Communication. https://edis.ifas.ufl.edu/wc401